Formulation and Evaluation of Maggot Extract Nanocream (Hermatia illucens) as a Future Anti-Aging Candidate - Situmorang, Novidawati Boru; Marbun, Romauli Anna Teresia (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Premature aging is a serious problem, especially for women. Skin aging is mainly caused by solar radiation. Ultraviolet (UV) A and B rays from sunlight induce the formation of reactive oxygen species in the skin and cause oxidation. Antioxidants are compounds that can neutralize free radicals by slowing down oxidation reactions. Maggots are widely consumed by the public and used as topical medicines because they have high levels of lauric acid, which acts as an anti-inflammatory, antibacterial, and antiprotozoal. Purpose: to analyze the formulation of nanocream preparations, antioxidant activity and evaluate the physical stability of maggot extract nanocream. Research method: The method used was the maceration method with n-hexane, antioxidant testing using the 2,2-Diphenyl-1-picrylhydrazyl (DPPH) method, and testing the physical stability of the preparation. The results of the antioxidant activity test showed an IC50 value of maggot extract of 40.36 ± 1.21 µg / mL. Results: It shows that the sample has very strong antioxidant activity. Based on the organoleptic test, the nanoceram preparation in Formula 1, 2, 3 and 4 has a milky white color which is influenced by the difference in the amount of extract, a distinctive aroma and semi-solid consistency. The pH examination of nanocream preparation must be adjusted to the skin pH, which is 5-7. The results of the viscosity test on the maggot extract have met the requirements, which are 2,000-5,000 cps. Conclusion: formulation and evaluation of the nanocream extract meet the requirements as a good nanocream and have the ability as an anti-aging.